Betty Goodwin: Work Notes. ART GALLERY OF ONTARIO, TORONTO - Carter, Rodney G.S. (Archivaria, 2011)
Betty Goodwin: Work Notes. ART GALLERY OF ONTARIO, TORONTO. Mounted at the Art Gallery of Ontario, 22 September 2010–24 April 2011.